A new miniaturized wideband self-isolated two-port MIMO antenna for 5G millimeter-wave applications - Asma Khabba; Jamal Amadid; Layla Wakrim; Zakaria El Ouadi; Saida Ibnyaich; Ahmed Jamal Abdullah Al-Gburi; Abdelouhab Zeroual; Tole Sutikno (Universitas Ahmad Dahlan, 2023)
Nowadays, millimeter-wave frequencies present a catchy solution to securing the colossal data rate needed for 5G communications. Accordingly, this research deals with the conception of a novel orthogonal 2×2 multiple input, multiple output (MIMO) antenna design operating in the millimeter wave spectrum with quite small dimensions of 11×6×0.8 mm3. The single antenna element consists of a trapezoidal microstrip patch antenna built on the Rogers RT5880 laminate with a permittivity of 2.2 and tangent loss of 0.0009. A trapezoidal-slot ground plane is used to support the structure. The antenna resonates at 28 GHz with a large bandwidth of 4 GHz from 26 to 30 GHz, a good gain of up to 5 dB, and a high radiation efficiency of 99%. A strong isolation is achieved that surpasses 26 dB. Besides, a high diversity performance is achieved where the envelope correlation coefficient (ECC) is lower than 0.001, the diversity gain (DG) is greater than 10 dB, and the channel capacity loss (CCL) is no longer than 0.4 bit/s/Hz. The achieved outcomes prove the robustness of the suggested MIMO antenna and qualify it to be a strong candidate for 5G wireless devices.